2021
DOI: 10.1177/10760296211050923
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Using Vitamin K for the Correction of INR Elevation Secondary to Hepatic Disease in Critically ill Patients: An Observational Study

Abstract: Background Using vitamin K for correction of coagulopathy in critically ill patients is controversial with limited evidence. This study aims to evaluate the efficacy and safety of vitamin K in the correction of international normalized ratio (INR) elevation secondary to liver disease in critically ill patients. Method A retrospective study of critically ill patients with coagulopathy secondary to liver disease. The primary outcome was to evaluate the association between vitamin K administration and the inciden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…7 Despite limited evidence of benefit, routine administration is also justified given vitamin K's "low adverse risk" profile; however, recent data may question this statement as a recent study by Sulaiman and colleagues found worse outcomes associated with its use with respect to thrombosis, length of stay, and mortality in a critically ill population. 3 Finally, by continually focusing on vitamin K administration, clinicians may see reductions in INR and obtain a false sense of security of hemorrhage or thrombosis risk. The majority of hemorrhages in patients with cirrhosis originate not from a lack of procoagulant factors, but from increased portal pressures, and by focusing on interventions aimed at correction of a quantitative value (INR), we may miss the true culprit for disease pathogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7 Despite limited evidence of benefit, routine administration is also justified given vitamin K's "low adverse risk" profile; however, recent data may question this statement as a recent study by Sulaiman and colleagues found worse outcomes associated with its use with respect to thrombosis, length of stay, and mortality in a critically ill population. 3 Finally, by continually focusing on vitamin K administration, clinicians may see reductions in INR and obtain a false sense of security of hemorrhage or thrombosis risk. The majority of hemorrhages in patients with cirrhosis originate not from a lack of procoagulant factors, but from increased portal pressures, and by focusing on interventions aimed at correction of a quantitative value (INR), we may miss the true culprit for disease pathogenesis.…”
mentioning
confidence: 99%
“…Yet, we must acknowledge that the international normalized ratio (INR), while useful at stratifying disease severity, does not predict hemorrhage risk in cirrhosis and furthermore the correction of the value by administering hemostatic agents, including vitamin K, in nonbleeding patients does not convey benefit. 2,3 In addition, we must be wary in describing patients with known cirrhosis and elevated INRs as coagulopathic. The INR is designed to measure procoagulant clotting factor activity, which is diminished in patients with cirrhosis, but does not account for the reduction of protein C and S nor the upregulation of von Willebrand Factor and factor VIII which is common in this cohort.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the statement in the AGA clinical practice update regarding the use of PO vitamin K is not cited [AGA 2019]. Among the cirrhotic patients, vitamin K 10 mg IV for up to three days was reported as adequate to correct vitamin K deficiency [38] and this is often seen in clinical practice; however, significant reductions in INR were only observed after the first dose in a study by Sulaiman et al [39]. The monitoring of the initial doses of vitamin K is essential in helping to determine whether a patient is vitamin K deficient-if INR improves, this is indicative of vitamin K deficiency; if INR remains the same, further administration of vitamin K would likely not be beneficial.…”
mentioning
confidence: 99%
“…Meyer et al evaluated vitamin K administered orally or parenterally (IV or SQ), compared with no vitamin K administration, and similarly found no significant effect on INR (the mean decrease in those considered responders was 0.2) [43]. Most recently, Sulaiman et al showed that an initial dose of vitamin K was effective at reducing INR with a median decrease of 0.63 in critically ill adult patients with liver disease and a baseline INR of at least 1.5 [39]. Of note, subsequent doses of vitamin K were not associated with significant decreases in INR.…”
mentioning
confidence: 99%